2023
DOI: 10.1101/2023.01.11.523563
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Evolutionary history ofCastanea sativaMill. in the Caucasus driven by Middle and Late Pleistocene paleoenvironmental changes

Abstract: Due to global climate cooling and aridification since the Paleogene, the members of the Neogene flora were extirpated from the Northern Hemisphere or were confined to a few refugial areas. For some species, the final reduction/extinction came in the Pleistocene, but some others have survived climatic transformations up to the present. This has occurred in Castanea sativa, a species of high commercial value in Europe and a significant component of the Caucasian forest biodiversity. In contrast to the European r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(20 citation statements)
references
References 117 publications
0
20
0
Order By: Relevance
“…Consequently, C. sativa in the western range (West Georgia) and eastern range (East Georgia and Azerbaijan) in the South Caucasus grows under different precipitation conditions. Studies have shown that the neutral genetic diversity of sweet chestnut in the Caucasus and the Iberian Peninsula are organized along the precipitation gradient (Beridze et al, 2023; Míguez‐Soto et al, 2019). Beridze et al (2023) demonstrated a reduced gene flow between two major clusters covering the western and eastern parts of the species range in the Caucasus, corresponding to the two climatic groups defined in this study.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Consequently, C. sativa in the western range (West Georgia) and eastern range (East Georgia and Azerbaijan) in the South Caucasus grows under different precipitation conditions. Studies have shown that the neutral genetic diversity of sweet chestnut in the Caucasus and the Iberian Peninsula are organized along the precipitation gradient (Beridze et al, 2023; Míguez‐Soto et al, 2019). Beridze et al (2023) demonstrated a reduced gene flow between two major clusters covering the western and eastern parts of the species range in the Caucasus, corresponding to the two climatic groups defined in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, we know that accurate estimates of N e may be especially difficult in trees because some aspects of their population biology violate methodological assumptions of N e estimation (Santos‐del‐Blanco et al, 2022). The values presented here may be down‐biased because of spatially restricted sampling and the intensive gene flow (Beridze et al, 2023). Also, trees are assumed to be able to efficiently respond to selection despite low N e (Hoban et al, 2021) because of a unique set of life history traits and genetic architecture allowing them for rapid adaptation (Aitken et al, 2008; Petit & Hampe, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations